2018
DOI: 10.3390/economies6040062
|View full text |Cite
|
Sign up to set email alerts
|

Growth Effect of Public Debt: The Role of Government Effectiveness and Trade Balance

Abstract: A growing number of recent works support the idea of debt threshold level (turning point), above which debt starts reducing economic growth. However, estimated threshold varies sharply across studies and gives a little insight into what the optimal level of debt is. The point is that there is no single turning point that could be applied to all countries and a proper investigation is needed on factors, which shape the debt impact on growth. This study aims to investigate whether debt threshold level depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 68 publications
1
27
0
4
Order By: Relevance
“…In addition, when public debt can affect economic growth in both positive and negative directions, the non-linear relationship appears. The literature captured the threshold effect by including square term of debt in the growth equation (Ahlborn & Schweickert, 2016;Butkus & Seputiene, 2018) or by conducting the panel smooth transition regression (Chen, Yao, Hu & Lin, 2017;Karadam, 2018 Kim et al, 2017). The Reinhart-Rogoff hypothesis argued that public debt can positively affect economic growth if the debt to GDP level is lesser than 90% (Reinhart, Reinhart, & Rogoff, 2015).…”
Section: Empirical Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, when public debt can affect economic growth in both positive and negative directions, the non-linear relationship appears. The literature captured the threshold effect by including square term of debt in the growth equation (Ahlborn & Schweickert, 2016;Butkus & Seputiene, 2018) or by conducting the panel smooth transition regression (Chen, Yao, Hu & Lin, 2017;Karadam, 2018 Kim et al, 2017). The Reinhart-Rogoff hypothesis argued that public debt can positively affect economic growth if the debt to GDP level is lesser than 90% (Reinhart, Reinhart, & Rogoff, 2015).…”
Section: Empirical Workmentioning
confidence: 99%
“…Empirically, the evidence from previous literature demonstrated that the debt-to-GDP threshold for all countries is not necessarily 90%. The threshold can range from 15% (Butkus & Seputiene, 2018) up to 2000% (Pegkas, 2018).…”
Section: Empirical Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While some empirical studies confirm the adverse impact of government debt on growth (Rahman, Ismail & Ridzuan, 2019), a growing number of recent works investigate the aforementioned idea of optimal level of government debt and a non-linear, an inverted U-shaped debt-growth relationship. The point here is that there is no single turning point that could be applied to all countries (Bentour, 2018) and a proper investigation is needed into factors that shape the debt impact on growth (Butkus & Seputiene, 2018). Alfonso and Alves (2014) analyzed the effect of public debt on economic growth for annual and 5-year average growth rates, as well as the existence of non-linearity effects of debt on growth for 14 European countries from 1970 until 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A rising level of government debt can create a high level of risk for investments and even create difficulties for investors in the lending markets. In addition to this, it raises the issue of adequacy of the fiscal policy formulated by the government (Butkus and Seputiene 2018). Further, it also increases the level of fiscal deficit, which in turn leads to a rise in inflation in long term.…”
Section: The Impact Of the Rise In Government Debtmentioning
confidence: 99%